Memaknai Hospitalitas Kristen Berdasarkan Roma 12: 17-21 Dalam Mewujudkan Moderasi Beragama di Indonesia - Setblon Tembang; Rinaldus Tanduklangi (Sekolah Tinggi Teologi Injili Indonesia (STTII) Yogyakarta, 2024)
This research is motivated by the increasing conflict between religious communities. Therefore, moderate religious perspectives, attitudes, and practices are needed to prevent conflict between religious communities. In its implementation, a hospitality attitude is needed. This is descriptive qualitative research with data collection techniques through literature study and text mining using exegesis. This research aims to provide insight into moderate Christian hospitality regarding superior attitudes in congregations and radicalism experienced by Roma congregations, which can be implemented to realize religious moderation in Indonesian society to maintain a harmonious and constructive life without discrimination. Based on a theological study of Romans 12: 17-21, Christians are called to live out Christian hospitality to create good relationships without discriminating against the background. Moderate Christianity can be realized through Christian hospitality by not returning evil for evil but returning evil for good. Christians are called to bring about peace with all people based on love. Therefore, Christians must practice hospitality in their lives in building and practicing a moderate life in religion, especially in the multi-religious context of Indonesia. This research can be developed in the form of a participatory study to see to what extent Christians' understanding of hospitality is embodied in realizing a moderate life in a multireligious society.